2018
DOI: 10.1017/s1047951118000392
|View full text |Cite
|
Sign up to set email alerts
|

A protocol to decrease postoperative chylous effusion duration in children

Abstract: Adoption of a chylothorax management protocol is feasible, and in our small cohort of patients implementation led to a significant decrease in the duration of chest tube utilisation, while eliminating practice variability among providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…MCT and 9 days in TPN (P > .05), which was similar to reports by Yeh et al [2013] and Winder et al [2018]. The length of hospital stay was significantly shorter in the EN with MCT group, partly because of the shorter time of chest tube utilization.…”
Section: E906supporting
confidence: 87%
See 1 more Smart Citation
“…MCT and 9 days in TPN (P > .05), which was similar to reports by Yeh et al [2013] and Winder et al [2018]. The length of hospital stay was significantly shorter in the EN with MCT group, partly because of the shorter time of chest tube utilization.…”
Section: E906supporting
confidence: 87%
“…The nutrition support costs in the EN with MCT group were lower than in the TPN group (P = .000), but the difference in total costs during hospitalization was not significant. Chylothorax has been diagnosed a median of 4 to 9 days after surgery [Chan 2010;Chan 2006;Winder 2018;Yeh 2013]; in our study, it 6 days in both groups. The length of PICU stay was a median of 8 days in EN with…”
Section: Discussionsupporting
confidence: 46%
“…Protocol-based management has been proposed to improve the outcomes of chylothorax, and studies have shown that implementing such management strategies led to reductions in chest tube utilization time and improvements in clinical outcomes [12][13][14]. We developed a management protocol and implemented it in September 2014.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite a liberal manner to step “back and forth” on the intensity of fat restriction without using a standard fixed protocol. Strategies that have been successful in shortening time to resolution of chylothorax and chest tube utilization in the pediatric population are specific steroids (hydrocortisone, dexamethasone, and methylprednisolone) and furosemide ( 14 ), thoracic duct embolization ( 9 , 15 , 16 ) and protocolized management ( 9 , 17 ). Most protocols categorized the severity of chylothorax by the volume of chyle output, using a cut-off of 20 mL/kg/day.…”
Section: Discussionmentioning
confidence: 99%